Challenges and Outlook of Veterinary Education in Iran: A Survey of Veterinary Students at Urmia University During the COVID‐19 Pandemic - Mojtaba Hadian; Bahram Dalir‐Naghadeh (Veterinary Medicine and Science)
ABSTRACT Background Veterinary science remains a challenging and less appreciated subject in the Iranian higher education system and society. Objectives This survey aimed to assess the satisfaction and outlook of veterinary students at Urmia University, one of the major veterinary faculties in Iran. The survey was conducted during the COVID‐19 pandemic, which also significantly impacted veterinary education. Methods A questionnaire was used to gather the opinions of 292 students. Results The results revealed that 50.2% of respondents were either completely unsatisfied or less satisfied with the quality of teaching. Poor clinical training, the curriculum and distance learning were identified as the primary reasons. In addition, 40.3% of students expressed a desire to change their major. Most students (82.6%) expressed a desire to continue their education after completing their undergraduate course. Regarding future employment, 45.8% of participants wanted to start their own business or practice, whereas 54.2% preferred employment opportunities. A significant 81.6% of participants said they would consider emigrating to pursue better career prospects. Conclusion The study highlighted various challenges in veterinary education in Iran, including dissatisfaction with the quality of teaching, an oversupply of trained veterinarians and limited career options. The COVID‐19 pandemic and distance learning further exacerbated these issues.